Tinjauan Yuridis Tindak Pidana Terhadap Terdakwa Memberikan Keterangan Palsu Demi Kepentingan Diri - Zainab Ompu Jainah; Zainudin Hasan; Gusti Wahyu Triyadi (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
Witness testimony according to Article 1 number 27 of the Criminal Procedure Code is one of the means of evidence in a criminal case which is in the form of information originating from a witness regarding a criminal event which the incident was witnessed, heard by oneself, and experienced by oneself accompanied by mentioning reasons and knowledge. That. A false statement under oath is that a person has sworn before giving a false statement or it can also be interpreted that under oath a person gives a statement first and then it is confirmed by oath. There is a case of perjury and perjury that occurred in the jurisdiction of Pesawaran, Lampung province. A defendant has committed the crime of giving false information for his own sake. Factors causing the defendant to commit the crime of providing false information for his own benefit based on court decision number 20/Pid.B/2023/PN Gdt which provided false information in making a report that the loss of 1 (one) motorbike at the Tegineneng Police was a false report. The Defendant was afraid that he would not be able to continue with the monthly installments because the Defendant's motorcycle was still on leasing credit and the Defendant intended that the police report that the Defendant made could be used as a basis for disbursing insurance.